Institutions postsecondaires françaises et pratiques d’internationalisation différenciées : analyse à partir du programme européen de doctorat international en réseau ERASMUS MUNDUS - Magali Hardouin (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
enThe paper questions the uneven access of higher institutions to the process of internationalization by updating practices, mindsets and strategies of institutions which reveal various degrees of international openness.The analysis of the differentiated involvement of French higher institutions in the European doctorate program ERASMUS MUNDUS allows some distancing from current rhetoric and slogans serving performative functions such as « World-class university ». The objective is to understand what prompted some higher education establishments to collaborate to create common doctorates and offer the training, and on the contrary, what prevented others from doing so.